Patrones socio-culturales del uso de drogas - Míguez L., Hugo Adolfo (Presidencia de la Rep. Oriental del Uruguay, Junta Nacional de Prevención y Represión del Tráfico Ilícito y Uso Abusivo de Drogas, 1993)
"Interesting use of participant observation to evaluate drug consumption patterns among youth in Punta del Este and surrounding communities. Provides detailed observations, but makes few references to relevant literature"--Handbook of Latin American Studies, v. 57